Exploring the Socio-Phenomenological Method in Qur'anic Interpretation: Hasan Hanafi's Approach - Solehuddin Solehuddin; Amalia Lailatul Muna (UIN Sunan Gunung Djati Bandung, 2023)
The primary objective of Qur’anic interpretation is to address its pressing significance, necessitating meticulous analysis. Hasan Hanafi seeks to overturn the classical approach, where interpretation starts from the Qur’an and moves towards understanding reality, by proposing a reverse trajectory, from reality to the text. This research delves into the methodological framework of Hanafi’s socio-phenomenological approach to Qur’anic interpretation. The socio-phenomenological approach, rooted in philosophy and social sciences, is employed as a tool for engaging with the Qur’an. Its aim is to mitigate subjectivity and prioritize the urgency of addressing communal concerns through interpretive studies. Content analysis is the research methodology employed, specifically employing descriptive analysis to comprehensively scrutinize the data at hand. A thorough library research method was implemented, encompassing an extensive survey of meticulously selected literature. The findings reveal that Hasan Hanafi’s interpretation aligns with the fundamental thematic method but adopts a more eclectic approach. Hanafi places greater emphasis on the pressing interests and challenges faced by the community, which are then confronted with the Qur’an in search of solutions. By emphasizing the relevance of the Qur’an to the social realities and phenomena of contemporary society, Hanafi’s method advocates for a dynamic and contextually sensitive interpretation that addresses the community’s urgent needs and problems. This study highlights the strengths of the socio-phenomenological approach, notably its capacity to provide holistic and profound understandings of social contexts and phenomena. Through its engagement with diverse disciplines and perspectives, this method encourages a comprehensive interpretation that takes into account the multidimensional nature of social issues.